Quand l'enseignement des sciences fait évoluer les idées des élèves au sujet de la pollution et de la santé - Diane Pruneau; Joanne Langis; Jean-François Richard; Guylaine Albert (VertigO)
Children are more vulnerable to environmental pollutants than adults and they have to, by consequence, be aware of the local dangers that threaten their health. In a polluted village, the researchers identified the initial conceptions of 9-10 year old students on pollution, health and the pollution-health link. They then helped the children live-through a process of conceptual change that included the expression, explanation, the comparison and writing of their conceptions, a reflexive observation of their milieu, a comparison of their ideas with that of a scientist and the transfer of new knowledge by communicating and doing an environmental action. After the project, students' conceptions on pollution have broadened all the while conserving the idea that pollution is something perceived by the senses. They were better able to name characteristics of a healthy person and to identify the possible effects of local pollutants on their health.